Development of a prototype of a low-cost sound intensity probe - Peixoto, Daniel Henrique N.; Magalhães, Max de Castro; Papini, Guilherme de Souza (Seven Editora, 2023)
The sound intensity is a vector quantity equal to the product of the sound pressure by the particle velocity vector, being used, mainly, for identification and characterization of sound sources. The sound intensity probes called "p-p" use two pressure transducers, installed very close to each other, to obtain the particle velocity by employing a finite difference approximation to the local spatial gradient of sound pressure. This work has as its main objective to present a low-cost p-p sound intensity probe prototype, built with 3D printing aid and measuring equipment available at UFMG: two preamplified microphones and an acquisition board. MATLAB software was also used, in which a signal processing was implemented to correct the phase difference between the acquisition channels and to calculate the sound intensity. All experiments performed with the intention of validating the sound intensity probe prototype are also presented together with their results, which were quite consistent with the theory studied. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-021